Pathogenesis Aspects of Microvascular Complications in Diabetic Retinopathy: Narrative Literature Review - Olga Simó-Servat; Cristina Hernández; Rafael Simó (Archives of The Medicine and Case Reports, 2022)
Chronic hyperglycemic conditions in diabetes mellitus can cause changes that result in chronic complications, both macrovascular and microvascular. There are several mechanisms thought to cause microvascular damage and retinopathy in diabetes, namely the polyol pathway, formation of advanced glycation end products (AGE), activation of protein kinase C (PKC), oxidative stress, and increased activity of the hexosamine pathway.